Reality counseling: enhancing the wife's role in the home - Triska Nofa Yuli; Yeni Karneli (International Journal of Technology, Innovation and Humanities, 2020)
Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on the Godhead of the Almighty. The wife has a very important role, namely as a companion to the husband at all times and mothers who are ready to look after and guide their children. The wife also acts as a partner or a good partner and fun for her life partner. The wife can be invited to discuss various kinds of problems that occur and also talk about light things. The phenomenon encountered in the field of a client who does not carry out his role as a wife because he feels the husband's treatment is not as sweet as when he was dating so that the client feels sorry for the marriage, this will have an adverse effect on the marriage relationship both in the short and long term. This can be helped by reality counseling by developing conditions of 3R Right, Reality and Responsibility and changing failure identity into success identity. So the client can accept the truth that already exists in accordance with existing norms, accept the fact that the client is married and the client is responsible for it. This research is a qualitative research using a case study approach with a subject, a 43 year old client. Data obtained through observation, interviews and data related to the client. The results of this study indicate that reality counseling can increase the role of the wife in the household.